RANCANG BANGUN COMPANY PROFILE BERBASIS WEB UNTUK EFISIENSI PENYAJIAN INFORMASI PADA SMA ANTARTIKA SIDOARJO - Murti, Brian Nusual Karyana; Hariadi, Bambang; Shintawati, Rahayu Arya (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
This research aims to design and build a web-based Company Profile SMA Antartika Sidoarjo. This study uses the Web Development Life Cycle (WDLC). This website has a frame which is divided into three parts: header that contains the logo SMA Antartika Sidoarjo and menus on the website, then the Content that contains company profile, school information, galleries, facilities and new student enrollment. The results of evaluation of the website Company Profile SMA Antartika Sidoarjo shows that website easy to use by the user in managing websites, has features that are useful to find out information about school/new student enrollment and fast in accessing the website. Based on the findings of this study suggested adding E -Learning feature so that business processes and learning that takes place in SMA Antartika Sidoarjo can be better integrated and efficient.